Von der Schule in die Berufsausbildung Soziale Konstruktionen durch Lehrkräfte über ungünstige Faktoren in der Bildungsbiografie von Schülerinnen und Schülern - Epp, André (Qualitative Fall- und Prozessanalysen. Biographie - Interaktion - soziale Welten, 2017)
The transition from school to the world of work is a challenging process for students, in which they also receive special support from teachers. On the basis of expert interviews, the qualitative study examines the theories that teachers have regarding the successful or less successful management of students' transition into training and professional practice. These (professional) knowledge structures are not only critically reflected, but also scanned for the presence or absence of an idea of ​​the biographical work of the students in the transition process.